Clinically stable very low birthweight infants are at risk for recurrent tissue glucose fluctuations even after fully established enteral nutrition. Issue 2 (7th November 2014) - Mola-Schenzle, E; Staffler, A; Klemme, M; Pellegrini, F; Molinaro, G; Parhofer, K G; Messner, H; Schulze, A; Flemmer, A W
Abstract : Objective: In previous cases, we have observed occasional hypoglycaemic episodes in preterm infants after initial intensive care. In this prospective study, we determined the frequency and severity of abnormal tissue glucose (TG) in clinically stable preterm infants on full enteral nutrition. Methods: Preterm infants born at <1000 g (n=23; G1) and birth weight 1000–1500 g (n=18; G2) were studied at a postmenstrual age of 32±2 weeks (G1) and 33±2 weeks (G2). Infants were fed two or three hourly, according to a standard bolus-nutrition protocol, and continuous subcutaneous glucose measurements were performed for 72 h. Normal glucose values were assumed at ≥2.5 mmol/L (45 mg/dL) and ≤8.3 mmol/L (150 mg/dL). Frequency, severity and duration of glucose values beyond normal values were determined. Results: We observed asymptomatic low TG values in 39% of infants in G1 and in 44% in G2. High TG values were detected in 83% in G1 and 61% in G2. Infants in G1 experienced prolonged and more severe low TG episodes, and also more frequent and severe high TG episodes. In G1 and G2, 87% and 67% of the infants, respectively, showed glucose fluctuations characterised by rapid glucose increase followed by a rapid glucose drop after feeds. In more mature infants, glucose fluctuations were less pronounced and less dependent on enteral feeds. Conclusions: Clinically stable well-developing preterm infants beyond their initial period of intensive care show interstitial glucose instabilities exceeding values as low as 2.5 mmol/L and as high as 8.3 mmol/L. This novel observation may play an important role for the susceptibility of these high-risk infants for the development of the metabolic syndrome. Trial registration number: German trial registration number DRKS00004590.